Pengaruh Ukuran Perusahaan, Struktur Modal, Pertumbuhan Penjualan, dan Biaya Lingkungan terhadap Nilai Perusahaan pada Sektor Basic materials yang Terdaftar di BEI Periode 2020-2024 - Serly Ismawati; Dianing Widya Kusumastuti (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This research seeks to investigate the impact of company size, capital structure, sales growth, and environmental costs on corporate value within the basic materials industry registered on the Indonesia Stock Exchange from 2020 to 2024. A quantitative method utilizing multiple linear regression was employed across 24 companies, yielding 120 observations. The outcomes indicate that company size and capital structure exert a notable influence on corporate value, whereas sales growth and environmental costs demonstrate no substantial effect. These results align with Signaling and Trade-Off Theories, highlighting how robust assets and effective funding strategies can boost investor confidence. Nevertheless, the Indonesian capital market has yet to completely incorporate environmental expenditures as a key driver of corporate value. The research suggests that enhanced openness in sustainability reporting is crucial for bolstering credibility and enduring corporate worth.